Decoding VExUS: a practical guide for excelling in point-of-care ultrasound assessment of venous congestion - Taweevat Assavapokee; Philippe Rola; Nicha Assavapokee; Abhilash Koratala (The Ultrasound Journal)
Abstract Venous congestion, often associated with elevated right atrial pressure presents a clinical challenge due to its varied manifestations and potential organ damage. Recognizing the manifestations of venous congestion through bedside physical examination or laboratory tests can be challenging. Point-of-care ultrasound (POCUS) is emerging as a valuable bedside tool for assessing venous congestion, with the Venous Excess Ultrasound (VExUS) technique gaining prominence. VExUS facilitates non-invasive quantification of venous congestion, relying on measurements of the inferior vena cava (IVC) size and Doppler assessments of the hepatic vein (HV), portal vein (PV), and intrarenal vein, thereby providing real-time insights into hemodynamic status and guiding therapeutic interventions. The grading system outlined in VExUS aids in stratifying the severity of congestion. However, achieving proficiency in VExUS requires a comprehensive understanding of Doppler techniques and their clinical applications. This review article provides practical guidance on performing VExUS, encompassing equipment requirements, preparation, machine settings, and examination techniques for assessing the inferior vena cava (IVC), hepatic vein (HV), portal vein (PV), and intrarenal vein. Potential pitfalls and troubleshooting strategies are discussed to ensure accurate interpretation of Doppler waveforms.